Factors influencing customers' loyalty of mobile service provider among generation Y - Al-Refai, Abdalla Nayef Saleh (2015)
Mobile phones are often known as a medium of self-expression and individuality for the younger generation. Generation Y is an important target market for mobile phone service providers. In the Jordanian market, the mobile phone service providers are facing a very competitive environment and many studies have shown that maintaining customer loyalty is a very challenging task for marketers nowadays. Therefore, the objective of this study was to investigate the factors that influence customer loyalty towards mobile phone service provider among Generation Y in Jordan. The current study examined the relationships between service quality, perceived value, perceived enjoyment and technological perceptions, and customer loyalty. The study also examined the role of customer satisfaction as a mediating variable and trust as a moderating variable between satisfaction and customer loyalty. A survey was conducted among 541 respondents in the Generation Y category in Jordan. Data was analyzed using partial least squares-structural equation modeling (PLS-SEM). The analyses revealed significant relationships between service quality, perceived enjoyment, technological perceptions and customer satisfaction, and customer loyalty, but the relationship between perceived value and customer loyalty was not significant. In addition, customer satisfaction mediated the relationship between service quality, perceived value and perceived enjoyment, and customer loyalty. On the other hand, customer satisfaction did not mediate the relationship between technological perceptions and customer loyalty. Moreover, trust did not moderate the relationship between satisfaction and customer loyalty. This study offers several implications on how managers of mobile phone service providers can ensure the long-term success relationship of their customer in light of the strong competitive advantage. In future studies, it would be interesting to include more variables to represent the entire relationship on customer loyalty towards Generation Y in mobile phone operators.